Antibiotic Resistances of Enterobacteriaceae with Chromosomal Ampc in Urine Cultures: Review and Experience of a Spanish Hospital - Enrique Rodríguez-Guerrero; Horacio Requena Cabello; Manuela Expósito-Ruiz; José María Navarro-Marí; José Gutiérrez-Fernández (MDPI AG, 2023)
The Enterobacteriaceae Citrobacter freundii, Enterobacter cloacae, Klebsiella aerogenes, Morganella morganii, Providencia stuartii, and Serratia marcescens (CESPM group) produce numerous urinary tract infections (UTIs) which are difficult to treat due to their high multiresistance rate. The objectives of this study were to carry out a systematic review of antibiotic resistances by UTIs and to determine changes over time in urine cultures from a reference hospital in southern Spain. The literature was searched for European data on the resistance rates of each microorganism, and a retrospective cross-sectional descriptive study was performed in samples with suspicion of UTI from patients in Virgen de las Nieves University Hospital (Granada, Spain) between 2016 and the first half of 2021. Among 21,838 positive urine cultures, 1.85% were caused by E. cloacae, 0.77% by M. Morganii, 0.65% by K. aerogenes, 0.46% by C. freundii, 0.29% by P stuartii, and 0.25% by S. marcescens. The lowest resistance rates by microorganism were: E. cloacae to amikacin (3.47%) and imipenem (5.28%); M. morganii to piperacillin-tazobactam (1.79%), cefepime (4.76%), and tobramycin (7.74%); K. aerogenes to tobramycin (3.55%), gentamicin (4.25%), trimethoprim-sulfamethoxazole (4.96%), imipenem (5.75%), and cefepime (6.43%); C. freundii to imipenem (no resistance), nitrofurantoin (1.96%), fosfomycin (2.80%), and ertapenem (6.12%); P. stuartii to cefepime (3.28%) and ceftazidime (3.28%); and S. marcescens to gentamicin (1.8%), ciprofloxacin (3.64%), cefepime (3.70%), piperacillin-tazobactam (3.70%), and trimethoprim-sulfamethoxazole (5.45%). In our setting, CESMP Enterobacteriaceae showed the lowest resistance to piperacillin-tazobactam, cefepime, imipenem, gentamicin, and colistin, which can therefore be recommended for the empirical treatment of UTIs. The COVID-19 pandemic may have had a clinical impact in relation to the increased resistance of E. cloacae and M. morgani to some antibiotics.